Impaired Immune Responses and B-Cell Proliferation in Mice Lacking the Id3 Gene - Pan, Lihua (American Society for Microbiology, 1999)
B-lymphocyte activation and proliferation induced by the B-cell receptor (BCR) signals are important steps in the initiation of humoral immune responses. How the BCR signals are translated by nuclear transcription factors into cell cycle progression is poorly understood. Id3 is an immediate-early gene responding to growth and mitogenic signals in many cell types including B cells. The primary function of the Id3 protein has been defined as that of inhibitor of basic-helix-loop-helix (bHLH) transcription factors. The interaction between Id3 and bHLH proteins, many of which are essential for cellular differentiation, has been proposed as a key regulatory event leading to cellular proliferation instead of differentiation. To further investigate the role of Id3 in tissue and embryo development and the mechanism of Id3-mediated growth regulation, we generated and analyzed Id3-deficient mice. While these mice display no overt abnormality in tissue and embryo development, their humoral immunity is compromised. The amounts of immunoglobulins produced in Id3-deficient mice immunized with a T-cell-dependent antigen and a type 2 T-cell-independent antigen are attenuated and severely impaired, respectively. Further analysis of lymphocytes isolated from Id3-deficient mice reveals a B-cell defect in their proliferation response to BCR cross-linking but not to lipopolysaccharide or a combination of BCR cross-linking and interleukin-4. Analyses of cultured lymphocytes also suggest involvement of Id3 in cytokine production in T cells and isotype switching in B cells. Finally, the proliferation defect in Id3-deficient B cells can be rescued by ectopic expression of Id1, a homologue of Id3. Taken together, these results define a necessary and specific role for Id3 in mediating signals from BCR to cell cycle progression during humoral immune responses.